Sustainable and recyclable thermosets with performances for high technology sectors. An environmental friendly alternative to toxic derivatives - Dinu, Roxana; Lafont, Ugo; Damiano, Olivier; Mija, Alice (Frontiers in Materials, 2023)
This study focuses on the development of environmentally friendly and chemically recyclable thermosets using or a renewable based monomer, the triglycidyl ether of phloroglucinol (TGPh), or a commercial non-toxic tris(4-hydroxyphenyl) methane triglycidyl ether (THPMTGE) monomer. The recyclable polyester thermosets were prepared by crosslinking the two monomers with hexahydro-4-methylphthalic anhydride (HMPA) or methyl nadic anhydride The TGPh-based formulations exhibited lower reaction temperatures and narrower reaction intervals. Additionally, these systems showed higher tan δ values (189°C–199°C), higher crosslinking densities (7.6–7.8 mmol cm−3) and compact networks, crucial for high-performance industries. Tensile tests demonstrated the remarkable mechanical properties of the thermosets, including high Young modulus (1.3–1.4 GPa), tensile stress (55–69 MPa), and an elongation at break around 3%–8%. Moreover, the thermosets exhibited complete dissolution at a temperature of 170°C, with depolymerization times of approximately 2.5 h for TGPh-based resins and 4.5 h for THPMTGE-based formulations. In conclusion, this study shows that sustainable and eco-friendly thermosets with excellent physico-chemical and thermo-mechanical properties, low hydrophilicity, and rapid dissolution capacity can be developed. These thermosets offer a viable alternative to non-recyclable and toxic resins in high-end industrial applications.